Evaluation of Bromelain, A Pineapple Extract as a Bleaching Agent on Human Enamel and Determining its Concentration by Reverse-HPLC Method - Ramya Sheshadri; Ashwini Tumkur Shivakumar; Bhaskaran Mahendran; Ravandur Shivanna Chandan; Sowmya Halasabalu Kalgeri (Wolters Kluwer Medknow Publications, 2023)
Introduction: In recent times, there has been an increase in the number of esthetic smile makeovers. As a part of these procedures, achieving a brighter smile is considered essential. The treatment options for such makeovers range from simple bleaching to complex restorations. Bleaching, a conservative and straightforward method to manage discolored teeth, has become popular. Therefore, vital bleaching has gained immense popularity. To evaluate and compare the color changes on human enamel bleached with different concentrations of hydrogen peroxide, containing pineapple extract as an additive, and determine the bromelain content in pineapple, by reversed-phase ‑ HPLC method. Material and Methods: Twenty permanent single-rooted artificially stained maxillary anterior teeth were decoronated at CEJ, the crown component was divided into two vertical halves, further divided into four groups containing 10 samples each and bleached accordingly. Group I (A) 15% H2O2 only, Group I (B) 2 mL of pineapple extract and 28 mL of 15% H2O2. Group II (A) 25% H2O2 only and Group II (B) 2 mL of pineapple extract and 28 mL of 25% H2O2. The samples were checked for color change with the help of a reflectance spectrophotometer. RP-HPLC method was used to find the proportion of bromelain in pineapple extract. Statistical analysis: carried out using one-way ANOVA for comparison between two groups and Scheffe's post hoc test for comparison between more than two groups. "Significance level" for all statistical tests was set at P < 0.05 (significance level <5%). All these analyses were carried out using the SPSS Version 22 software. Results: Group II B showed the maximum change in color means ΔE compared to the other three groups. The mean color change ΔE between Group II A and ΔE Group I B showed no statistical difference. The mean color change ΔE of Group I A showed the least color change compared to all other groups. Group II B showed a statistically significant change in color with "P −0.001" compared to all other groups. Linearity overlay on chromatogram by RP-HPLC method showed the concentration of bromelain in pineapple extract is 64.99 mcg/mL. Conclusion: Pineapple extracts along with hydrogen peroxide showed promising results with a new gateway of success in whitening teeth.